Isu sosioemosi dalam kalangan pelajar sekolah rendah di negeri Sabah (socioemotional issues among primary school students in Sabah) - Jusiah Idang; Hanisah Halim; Murnizam Halik; Sabariah Sharif (Universiti Kebangsaan Malaysia, 2021)
This study aims to identify socio-emotional issues that often exist among primary school students, especially in the state of Sabah. The respondents involved were a total of 580 people consisting of teachers in several schools from all over Sabah. Respondents as class teachers are required to evaluate and identify socio-emotional issues that often occur among students based on the questionnaire provided. After analysis, the results showed that the majority of 59.8% or 347 respondents have chosen the answer that shows that various socio-emotional issues exist simultaneously at one time. The issues identified have involved more than one pair of issues for a class that has been assessed by the respondents. Next, 16.9% of respondents chose the issue of “emotional behavior disorder”, 8.8% of respondents chose the issue of “changes in the family (divorce, separation)”, 6.2% chose the answer of “being alone with peers”, and 4% chose the issue of “bullying”. The issue of "autism" was realized by 1% of respondents, while 0.7% reported that there was an issue of "death among family members" of their students which caused the socio-emotional level of the students involved. The remaining 2.6% of respondents were aware that all the issues suggested in the answers had been experienced by their students. It is hoped that this study can be used as a guide to understanding more specifically the conflicts that are often experienced by children who are in early school life.